Financial Literacy as a Mediator: Entrepreneurial Orientation and Fintech Adoption on MSME Financial Performance in Kediri - Ahmad Munif; Ahmad Yani; Ahmad Idris; Galuh Nuril Lathifah (Program Studi Ekonomi Syariah, FEBI UIN Datokarama Palu, 2026)
Despite the growing adoption of financial technology and entrepreneurial practices among MSMEs, limited attention has been given to the mechanisms through which these capabilities improve financial performance. This study examines the role of financial literacy as a mediating mechanism linking entrepreneurial orientation, fintech adoption, and MSME financial performance in Kediri City. Using a quantitative explanatory approach, data were collected from 195 MSMEs and analyzed using PLS-SEM. The findings show that entrepreneurial orientation positively affects financial literacy but does not directly affect financial performance. In contrast, fintech adoption has a significant direct effect on both financial literacy and financial performance. Financial literacy significantly improves financial performance and serves as a full mediator between entrepreneurial orientation and financial performance, and as a partial mediator between fintech adoption and financial performance. The study concludes that financial literacy is a key mechanism through which entrepreneurial and technological capabilities are translated into financial outcomes. This study contributes to MSME performance literature by integrating financial literacy into a mediation framework and offers practical implications for policymakers, financial institutions, and fintech providers in strengthening financial capability, digital adoption, and inclusive MSME empowerment.